Variasi Konsentrasi Aktivator Asam Sulfat (H2SO4) pada Karbon Aktif Ampas Tebu Terhadap Kapasitas Adsorpsi Logam Timbal - Asrijal, Asrijal; Chadijah, St; Aisyah, Aisyah (Al-Kimia, 2014)
Bagasse is a waste-disposal which can contaminate the ambient surroundings. In order to ward off the massive impact, a method which is considered to be good is that to turn it into adsorbent in a process of lead-metal adsorption. This research aims to know the concentration of lead-metal that can be adsorbed by an active carbon and to know the effect of H2SO4 activator on the adsorption capacity of bagasse towards the lead-metal. The activated carbon, was derived from bagasse in three phases namely preparation, carbonization, and activation. The bagasse was carbonized in temperature of 400oC. It was then activated by H2SO4 in concentration of (0%, 5%, 10%, 15%, and 20%) for 24 hours, and heated to 500 oC. The adsorption was performed during one hour by utilizing 150 rpm shaker. The analysis of lead concentration using atom adsorption spectrophotometer (AAS) showed that the inactivated carbon performed the best adsorption with the concentration of lead adsorbed was to 9.8485 mg/L and the capacity of adsorption was to 0.197 mg/g.